The Impact of Orthognathic Surgery on Oral Health-Related Quality of Life - Reza Tabrizi; Arash Rezaii; Ali Golkari; Farzaneh Ahrari (Mashhad University of Medical Sciences, 2013)
Introduction: This study aimed to measure the changes in oral health-related quality of life of the patients, referred to Shahid Chamran Hospital in Shiraz before and after the orthognathic surgery. Methods: This prospective study was performed using the 14-item oral health impact profile (OHIP-14) questionnaire. The questionnaires were given both before and four months after the orthognathic surgery to all the patients referred to Shahid Chamran Hospital of Shiraz between 20th of November 2012 and 20th of February 2013. The patients were asked about their motivation for surgery and the responses were classified as functional, esthetic or a combination of functional and esthetic problems. The data achieved from all the questions before and after the surgery were analyzed using repeated measures test. Results: Twenty eight patients including 10 men and 18 women participated in this study. The mean scores of quality of life after the surgery decreased significantly compared to that before the treatment (P